2015
DOI: 10.1016/j.jaap.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of wood–PVC mixtures. Formation of chloromethane from lignocellulosic materials in the presence of PVC

Abstract: Thermal decomposition of polyvinylchloride (PVC) -wood and wood component mixtures were examined under slow and fast heating by pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) and thermogravimetry/mass spectrometry(TG/MS) techniques in order to clarify the chemical interaction of biomass materials and PVC during thermal decomposition. A hardwood and a softwood (beech and pine), their lignin and two types of cellulose (Avicel and Whatman) were chosen as natural polymer components. Comparing the gaseou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 21 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…The carbon yield was very similar to those found by Prabhavathi Devi and co-workers for carbons obtained from glycerol pitch [25]. The yield obtained for other industrial wastes was similar to that reported by Czegeny and co-workers for lignocellulosic materials [26].…”
Section: Characterization Of the Carbonssupporting
confidence: 88%
“…The carbon yield was very similar to those found by Prabhavathi Devi and co-workers for carbons obtained from glycerol pitch [25]. The yield obtained for other industrial wastes was similar to that reported by Czegeny and co-workers for lignocellulosic materials [26].…”
Section: Characterization Of the Carbonssupporting
confidence: 88%
“…Such an effect is confirmed by the results of processing testing, i.e., a smaller maximum of torque recorded in comparison with the M X of unfilled PVC. Another explanation of this effect is proposed in [65]. The authors concluded that the methoxy groups in phenolic rings in lignin are the methyl source of chloromethane formation, and that this reaction consumes most of the HCl evolved from the PVC.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Another explanation of this effect is proposed in [65]. The authors concluded that the methoxy groups in phenolic rings in lignin are the methyl source of chloromethane formation, and that this reaction consumes most of the HCl evolved from the PVC.…”
Section: Polymers 2015 7 14mentioning
confidence: 99%
“…• pyrolysis-GC (pyrolysis at Curie point of 500 o C) to study volatiles composition, 82 • pyrolysis-GC-MS − gases from thermal decomposition, 311 • GC-MS is used for many purposes, such as volatile species formed during UV-irradiation, 312 dioxins in exhaust gas from incinerator, 313 vinyl chloride in water from water pipe, 17,314 low molecular weight plasticizers, 167 plasticizers in food and medical use, 77,315-319 plasticizer indoor emissions from wallpaper and flooring, 320 residual contents of plasticizers in wastes in landfills, 321 guide to identification of plasticizers can be found elsewhere, 322 additives in gaskets of lids for glass jars, 323 organotins in edible oils, 115 derivatized organotins by reaction with Grignard reagent or reduction to organotin hydrate, 325,326 dibutyltin in wine by solid-phase microextraction GC-MS. 327 Pyrolysis of wood-PVC mixtures 331 10.6.2 LIQUID CHROMATOGRAPHY High pressure liquid chromatography, HPLC, is mostly used in evaluation of low molecular weight compounds added to PVC, as follows:…”
Section: Chromatographic Methodsmentioning
confidence: 99%